THE CONCEPT OF TRANSCENDENTAL LOVE IN THE TAFSÄªR AL-QURÄ€N AL-Aáº’ÄªM BY AT-TUSTURIY - Labib, Hakki Akmal (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2018)
Abstract The concept of á¸¥hubb is closely related to daily life. Anyone must have love. Whether it's love from biological aspect, social aspect, or theological aspect. This is one of the reasons why researchers choose the term á¸¥hubb. And the other reasons are, first, the word á¸¥hubb is one of the key words in al-QurÄn that describes the concept of deed, whether it is the concept of worship, as well as the social concept beloved by God and it is important to be known as the sustainer of everyday life. Secondly, the translation of al-QurÄn gives only the earliest description of the meaning of the word á¸¥hubb only to the extent of the meaning of love, thus requiring a deeper explanation in order to know its meaning comprehensively. So, this study will discuss about the concept of á¸¥hubb according Sahl bin â€˜AbdullÄh at-TusturÄ« in TafsÄ«r al-QurÄn al-Aáº“Ä«m. He was known by a mutaá¹£awwÄ«f and mufassÄ«r